PERAN GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA DI SEKOLAH DASAR - Arini Sakinah (Journal of Education and Teaching Learning, 2023)
Learning motivation is a student's internal and external factors to change behavior. Thepurpose of this research is to find out how the teacher functions in the learning process, howthe teacher increases student learning motivation, the inhibiting factors of the teacher inincreasing student motivation and interest in learning and how the solutions that will becarried out by the teacher in increasing student learning motivation. The teacher's role inincreasing student learning motivation is one of the integral activities that must exist inlearning activities. The learning process will be successful if students always have motivationin learning. The teacher's role is to make students more diligent in learning with motivation,encouragement, and strategies carried out by the teacher to increase student motivation,because the teacher is the best motivator for students in increasing student motivation. Abstrak : Motivasi belajar merupakan faktor internal dan eksternal siswa untuk melakukan perubahanperilaku. Tujuan penilitian ini untuk mengetahui bagaimana fungsi guru dalam prosespembelajaran, cara guru dalam meningkatkan motivasi belajar siswa, faktor penghambat gurudalam meningkatkan motivasi dan minat belajar siswa serta bagaimana solusi yang akandilakukan oleh guru dalam meningkatkan motivasi belajar siswa. Peran guru dalammeningkatkan motivasi belajar siswa salah satunya kegiatan integral yang harus adadalam kegiatan pembelajaran. Proses belajar akan berhasil jika siswa selalu memiliki motivasidalam belajar. Peran guru adalah membuaat siswa lebih rajin belajar dengan motivasi,dorongan, dan strategi-strategi yang dilakukan oleh guru untuk meningkatkan motivasibelajar siswa, karena guru adalah motivator terbaik untuk para siswa dalammeningkatkan motivasi kepada siswa